Estimation of Potential Carbon Economic Value of Bamboo In Community Forest Area in Rumpin-Dalam Hamlet, Rumpin Village, Bogor District - Wijayani, Inggit Putri; Sasongko, Dwi Agus; Rusli, Abdul Rahman (Journal of Sylva Indonesiana, 2025)
Community forests represented one area that could be utilized in carbon trading. Rumpin-Dalam Hamlet had an area in the form of a community forest with a bamboo forest formation. The planned construction of the Serpong-Bogor toll road could result in the loss of part of the bamboo forest. This study aimed to determine the potential of bamboo, biomass, absorption, and economic value of carbon in the bamboo forest. The research procedure began with the determination and placement of plots in the bamboo forest. Biomass data collection occurred in a non-destructive manner (without causing damage). The next step was to calculate biomass, carbon stock, carbon sequestration, and the carbon economic value. The research results showed that there were five types of bamboo in the Rumpin-Dalam Hamlet Community Forest. These types included apus bamboo (Gigantochloa apus), mayan bamboo (Gigantochloa robusta), black bamboo (Gigantochloa atroviolacea), ater bamboo (Gigantochloa atter), and betung bamboo (Dendrocalamus asper). Bamboo forests in the area absorbed a carbon potential of 403.55 tCO2 and had a carbon economic value of US$ 20,177.5.